2014
DOI: 10.1242/jcs.125062
|View full text |Cite
|
Sign up to set email alerts
|

Nestin regulates prostate cancer cell invasion by influencing FAK and integrin localisation and functions

Abstract: BSTRACTNestin, an intermediate filament protein and marker of undifferentiated cells, is expressed in several cancers. Nestin is important for neuronal survival and is a regulator of myogenesis but its function in malignancy is ambiguous. We show that nestin downregulation leads to a redistribution of phosphorylated focal adhesion kinase (pFAK, also known as PTK2) to focal adhesions and alterations in focal adhesion turnover. Nestin downregulation also leads to an increase in the protein levels of integrin a5b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 79 publications
3
48
0
Order By: Relevance
“…However other controlling factors may also be at play, since in a mouse neuronal cell line histone acetylation, rather than DNA methylation, is required to regulate NES expression (Han et al , 2009). Whereas initial reports indicated that NES is involved in prostate cancer cell migration, invasion, and metastasis (Kleeberger et al , 2007), more recent work demonstrates an inhibitory role for NES in prostate cancer cell migration and invasion (Hyder et al , 2014). In the work by Hyder et al, (2014), decreased NES expression regulates phosphorylated focal adhesion kinase activity, integrin localization on the cell membrane, and extracellular matrix proteolysis resulting in larger cells that spread out upon the tissue culture growth surface and have increased invasive properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However other controlling factors may also be at play, since in a mouse neuronal cell line histone acetylation, rather than DNA methylation, is required to regulate NES expression (Han et al , 2009). Whereas initial reports indicated that NES is involved in prostate cancer cell migration, invasion, and metastasis (Kleeberger et al , 2007), more recent work demonstrates an inhibitory role for NES in prostate cancer cell migration and invasion (Hyder et al , 2014). In the work by Hyder et al, (2014), decreased NES expression regulates phosphorylated focal adhesion kinase activity, integrin localization on the cell membrane, and extracellular matrix proteolysis resulting in larger cells that spread out upon the tissue culture growth surface and have increased invasive properties.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas initial reports indicated that NES is involved in prostate cancer cell migration, invasion, and metastasis (Kleeberger et al , 2007), more recent work demonstrates an inhibitory role for NES in prostate cancer cell migration and invasion (Hyder et al , 2014). In the work by Hyder et al, (2014), decreased NES expression regulates phosphorylated focal adhesion kinase activity, integrin localization on the cell membrane, and extracellular matrix proteolysis resulting in larger cells that spread out upon the tissue culture growth surface and have increased invasive properties. Interestingly, the iAs transformed cells in our study often show a similar phenotype, with increased size, more extensive spreading, and increased invasion.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, synemin contributes to the migratory properties of astrocytoma by influencing focal adhesions through its specific interaction with zyxin [68] and also by controling actin dynamics [69]. Nestin is a specific regulator of FAK phosphorylation and VASP dynamics and thereby controls the invasive capacity of prostate cancer cells [70]. Keratins 6a and 6b (K6), the expression of which is rapidly induced in wound-proximal epidermal keratinocytes, directly interact with Src to prevent its activation during cell migration.…”
Section: Considered Too Inactive To Raise Suspicion: Ifs Participate mentioning
confidence: 99%
“…These pathological roles of nestin are supported by a similar study by other investigators. 57 In contrast, nestin is recognized as a cancer stem cell marker of prostate cancer, and there are several reports on nestin as a cancer stem cell. 58,59 However, unfortunately, there is no report regarding MVD measured by using anti-nestin antibody.…”
Section: Nestinmentioning
confidence: 99%